LEGAL PROTECTION OF PUBLIC INVESTORS WHO CONDUCT STOCK SPLIT BASED ON POJK NUMBER 15/POJK.04/2022 - Obaja Capandi Saut Horas Sinaga; Sunarmi; Robert (PT. Radja Intercontinental Publishing, 2024)
Legal Protection for Public Investors Carrying out Stock Splits Based on POJK Number 15/POJK.04/2022. In the capital market, public investors play an important role in providing funds for companies listed on the stock exchange. One strategy often used by companies to increase the liquidity of their shares is a stock split. However, stock splits also have risks for public investors. Therefore, adequate legal protection is needed for public investors who carry out stock splits. This research aims to analyze legal protection for public investors who carry out stock splits based on Financial Services Authority Regulation (POJK) Number 15/POJK.04/2022. The research method used is a normative juridical method with a statutory approach and case analysis. The research results show that POJK Number 15/POJK.04/2022 has provided sufficient legal protection for public investors. This protection includes the company's obligation to provide transparent and accurate information regarding the stock split, including the reasons and impact on share prices. Apart from that, POJK also regulates sanctions for companies that violate these provisions. However, this research also found that there are several weaknesses in the implementation of this regulation, such as a lack of supervision and strict law enforcement against companies that commit violations. Therefore, efforts are needed to increase supervision and law enforcement by the Financial Services Authority (OJK) to ensure effective legal protection for public investors. Thus, it is hoped that this research can contribute to improving legal protection for public investors who carry out stock splits, as well as providing input for the OJK in formulating better policies in the future.